Putative pore-loops of TMEM16/anoctamin channels affect channel density in cell membranes. - Adomaviciene, A; Smith, K; Garnett, H; Tammaro, P (2013)
The recently identified TMEM16/anoctamin protein family includes Ca(2+)-activated anion channels (TMEM16A, TMEM16B), a cation channel (TMEM16F) and proteins with unclear function. TMEM16 channels consist of eight putative transmembrane domains (TMs) with TM5-TM6 flanking a re-entrant loop thought to form the pore. In TMEM16A this region has also been suggested to contain residues involved in Ca(2+) binding. The role of the putative pore-loop of TMEM16 channels was investigated using a chimeric approach. Heterologous expression of either TMEM16A or TMEM16B resulted in whole-cell anion currents with very similar conduction properties but distinct kinetics and degrees of sensitivity to Ca(2+). Furthermore, whole-cell currents mediated by TMEM16A channels were ∼six times larger than TMEM16B-mediated currents. Replacement of the putative pore-loop of TMEM16A with that of TMEM16B (TMEM16A-B channels) reduced the currents by ∼six-fold, while the opposite modification (TMEM16B-A channels) produced a ∼six-fold increase in the currents. Unexpectedly, these changes were not secondary to variations in channel gating by Ca(2+) or voltage, nor were they due to changes in single-channel conductance. Instead, they depended on the number of functional channels present on the plasma membrane. Generation of additional, smaller chimeras within the putative pore-loop of TMEM16A and TMEM16B led to the identification of a region containing a non-canonical trafficking motif. Chimeras composed of the putative pore-loop of TMEM16F transplanted into the TMEM16A protein scaffold did not conduct anions or cations. These data suggest that the putative pore-loop does not form a complete, transferable pore domain. Furthermore, our data reveal an unexpected role for the putative pore-loop of TMEM16A and TMEM16B channels in the control of the whole-cell Ca(2+)-activated Cl(-) conductance.